Radioactivity and Hazard Indices of Soil Sample in Al-Dura thermal Power Plant in the Southern of Baghdad-Iraq - A. Hattab , Leena (Iraqi Journal of Science, 2023)
The presence of natural radioactivity in soil and other materials results in internal and external exposure in twelve samples at Al_Dura Heating generator at south of Baghdad using NaI(Ti) detector .Therefore, it is desirable to determine the concentration of naturally occurring radionuclide’s238 U 232Th and 40 K,.. natural radioactivity and associated radiation hazard in some soil samples. The natural radioactivity due to the presence of 238 U 232Th and40 K in soil samples was measured by gamma spectrometry using NaI(Tl) scintillation well-shaped detector. In this context, soil samples were collected from thirty different locations of southern Al-Dura thermal Power Plant.Radium equivalent activities were calculatedfor the analyzed samples to assess radiation hazards arising due to the presence of these radionuclide’s in the samples most of the calculated radium equivalent activities are lower than the limit set in the OECD report at 370 Bq/K.The measured representative level index values for the investigated samples varied in 1.035- 0.375 & 0.630- 0.1380 Bq/kg the range external and internal hazard index (Hex,Hin) , The radiation hazard indices of soilwas also lower than the maximum suggested global value the values of the Hex and Hin indices must be less than unity (˂1) for the radiation hazard to be negligible the specific dose rates indoor (D) and the annual effective dose (DE) due to gamma radiation from building materials was calculated.The value of the representative gamma index (Iγr) for the all soil samples were greater than the unity (>1).